Low Baseline but Not Delta Cortisol Relates to 28-Day Transplant-Free Survival in Acute and Acute-on-Chronic Liver Failure - Sofia Roth; Emilio Flint; Lea Ghataore; Vishal C. Patel; Arjuna Singanayagam; Royce P. Vincent; Evangelos Triantafyllou; Yun Ma; William Bernal; Georg Auzinger; Michael Heneghan; Charalambos Antoniades; et al. (Gastro Hep Advances, 2023)
Background and Aims: The clinical, prognostic, and therapeutic impact of adrenal insufficiency in acute liver failure (ALF) and acute-on-chronic liver failure (ACLF) remains controversial and exact diagnostic criteria are lacking. We sought to determine the diagnostic and therapeutic value of cortisol measurement and glucocorticoid (GC) treatment in ALF and ACLF. Methods: 28-day transplant-free survival (TFS) was studied in relation to absolute cortisol concentrations and to GC treatment in ALF (n = 30) and ACLF (n = 34) patients. Cortisol concentrations and short synacthen test were assessed by chemiluminescence immunoassay and liquid chromatography-mass spectrometry. Clinicians decided independently on GC treatment. In relation, phenotypic and functional characteristics of circulating monocytes were assessed. Results: In ALF, baseline cortisol concentrations <387 nmol/L predicted TFS (sensitivity 83%, specificity 53%). In ACLF, baseline cortisol <392 nmol/L correlated with TFS (sensitivity 80%, specificity 61%). In both, ALF and ACLF, GC treatment did not influence 28-day TFS in patients with low baseline cortisol. However, in patients with baseline cortisol exceeding 387 and 392 nmol/L, respectively, TFS was higher if they had been treated with GC. High baseline cortisol was associated with low HLA-DR expression on monocytes. Conclusion: Our data suggest a prognostic value of baseline cortisol measurement in ALF and ACLF. Overall, strong activation of the hypothalamic–pituitary–adrenal axis indicated poor prognosis. Furthermore, baseline cortisol deserves prospective evaluation as a guide for GC treatment decision-making.